Lower limits of fluorescein and indocyanine green dye for digital cSLO fluorescence angiography. Issue 12 (18th November 2005) - Bindewald, A; Stuhrmann, O; Roth, F; Schmitz-Valckenberg, S; Helb, H-M; Wegener, A; Eter, N; Holz, F G
Abstract : Background: With the advent of digital confocal scanning laser ophthalmoscopy it is possible to detect low levels of fluorescence. Here we used a novel confocal scanning laser ophthalmoscope (cSLO) to determine lower limits of dye required for fluorescein (FL) and indocyanine green (ICG) angiography. Methods: A cSLO (Heidelberg retina angiograph 2, Heidelberg Engineering, Dossenheim, Germany) with an optically pumped solid state laser (488 nm) for FL and a diode laser (790 nm) for ICG angiography (FL/ICG-A) was used. 62 FL-As were performed in 53 patients and 45 ICG-As were performed in 39 patients with neovascular age related macular degeneration. The volume and overall dye content of bolus injections was gradually tapered (FL: 500 mg, 250 mg, 200 mg, 166 mg, 100 mg; ICG: 25 mg, 20 mg, 15 mg, 10 mg, 5 mg, 2.5 mg), while dye concentrations were kept constant at 100 mg/ml for FL and at 5 mg/ml for ICG. Images were obtained 1, 5, 15, and 30 minutes after dye injection. Image quality was evaluated by two independent readers using standardised criteria. Results: For amounts down to 166 mg for FL and to 5 mg for ICG, sufficient image quality was achieved during all phases following injection. Only late phase images showed less contrast compared to typically used dye amounts, which was irrelevant for interpretation and clinical management. Conclusions: With the increased sensitivity of this novel cSLO system, amounts of injected dye during FL-A can be reduced to one third for FL and to one fifth for ICG without relevant loss of image quality or information compared to conventionally used dye levels. These amounts can be used for routine angiography and allow relevant savings for units performing FL-A.